2021
DOI: 10.1039/d1sc04369b
|View full text |Cite
|
Sign up to set email alerts
|

Visible light-induced oxidative N-dealkylation of alkylamines by a luminescent osmium(vi) nitrido complex

Abstract: N-Dealkylation of amines by metal oxo intermediates (M=O) is related with drug detoxification and DNA repair in biological systems. In this study, we report the first example of N-dealkylation of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…9 For instance, OsN* readily activates the aliphatic C–H bonds of hydrocarbons 9 a and undergoes N -dealkylation of tertiary amines. 10 We report herein unprecedented oxidative C–O cleavage of H 2 Cat/H 2 Q by OsN* , with concomitant conversion of the coordinated cyanide of the osmium complex to carbon monoxide (Fig. 1b).…”
mentioning
confidence: 74%
“…9 For instance, OsN* readily activates the aliphatic C–H bonds of hydrocarbons 9 a and undergoes N -dealkylation of tertiary amines. 10 We report herein unprecedented oxidative C–O cleavage of H 2 Cat/H 2 Q by OsN* , with concomitant conversion of the coordinated cyanide of the osmium complex to carbon monoxide (Fig. 1b).…”
mentioning
confidence: 74%
“…Different photochemical N -dealkylation methods using various photocatalysts have been developed for the synthesis of various N -dealkylated chemicals [ 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 ]. An early report by Pandey et al [ 160 ] showed that the photolysis of a tertiary N -methyl amine using dicyanonaphtalene 128a as electron acceptor in the presence of sodium hydroxide in methanol led to high yields of N -demethylated products ( 51c , 94c , 129c , and 130c ) ( Figure 18 ).…”
Section: Photochemical N -Dealkylationmentioning
confidence: 99%
“…3,4 High-oxidation-state metal complexes naturally have strong oxidizing ability; thus the rational design and synthesis of stable high-oxidation-state metal complexes to disturb the intracellular redox balance may have great application prospects. [5][6][7][8][9][10] In our studies, we demonstrated that the human trace element chromium (Cr) can be used as a metal center to construct a stable Cr(V) complex for efficient cancer therapy. The Cr(V) drugs react with GSH and catalyse hydrogen peroxide conversion to singlet oxygen to disturb the in vivo and in vitro redox balance from both oxidation and reduction.…”
mentioning
confidence: 95%